TET2 downregulation enhances the antitumor efficacy of CD19 CAR T cells in a preclinical model - Yeongrin Kim; Moonjung Jeun; Heung Kyoung Lee; Ji U Choi; Simon Park; Chi Hoon Park (Experimental Hematology & Oncology)
Abstract Chimeric antigen receptor (CAR) T cell therapy has demonstrated significant clinical efficacy in patients with hematologic cancers. However, long-term follow-up studies indicate that only 50% of patients remain in complete remission after three years. To overcome these limitations, we investigated a strategy to enhance the antitumor activity of CAR T cells through gene modification. Based on previous research results demonstrating that CAR T cells with disrupted TET2, a methylcytosine dioxygenase, exhibit enhanced antitumor effects compared to conventional CAR T, we developed CAR T cells in which TET2 is downregulated by TET2 shRNA. Among the screened TET2-specific shRNAs, TET2-shRNA-1 was identified as the most effective sequence for gene silencing. Using this sequence, we constructed an all-in-one vector co-expressing CD19 CAR and TET2 shRNA. In vitro studies demonstrated that TET2 knockdown CD19 CAR T cells exhibited comparable cytolytic activity against CD19-positive cancer cells compared to conventional CD19 CAR T cells. However, interestingly, in xenograft mouse model using NSG mice, TET2 knockdown CAR T cells showed significantly improved antitumor activity compared to conventional CAR T cells. Our study demonstrates that shRNA-mediated knockdown of TET2 is a promising strategy to enhance the antitumor activity of CD19 CAR T cells in a preclinical model.